English Meeting Club: Students’ Perception and Their Speaking Skill - Hijrah Hijrah; Nurul Hikmah Umar (Journal of Development Research, 2021)
This study aims to find out students’ perception of English meeting club to support their speaking skill. English meeting club was a club or group of humans with common ambitions or interests in English. This study focused on the students’ perception of English meeting club to support their speaking skill. The subject of this study are 10 students of English department as participants. This study used a qualitative method, this study used interview as research instrument. The result of interviews, the majority of the students had positive perception about joined in English club. The student absolutely believes if English club could support them to speak English fluently. The student also had a perception through an English meeting club as a media to develop skills particularly in speaking, it could be one of the alternatives for those who need to learn and practice more about how to speak English well and it can also enhance their ability to speak English fluently.